Treatment-resistant severe capecitabine-induced diarrhoea resolved with oral budesonide. Issue 11 (1st December 2019) - Shumar, John; Junga, Zachary; Johnson, Jeptha T; Goldkind, Lawrence
Abstract : Chemotherapy-induced diarrhoea (CID) is a risk of antineoplastic regimens, often associated with 5-fluorouracil (5-FU), irinotecan and capecitabine. Current treatment guidelines for CID include the use of loperamide and octreotide but do not account for other therapies, including budesonide. Small case reports have shown benefit with budesonide in CID secondary to 5-FU and irinotecan, but there is no literature base addressing budesonide use in CID secondary to capecitabine. We describe a case of a patient with severe capecitabine-induced diarrhoea that was refractory to guideline based therapy but resolved with the use of budesonide.